Acoustics and psychoacoustics - Howard, David M. (David Martin), 1956-; Angus, Jamie; ScienceDirect eBooks (Amsterdam ; Boston ; London : Focal, 2009)
The acoustics of a space can have a real impact on the sounds you create and capture. Acoustics and Psychoacoustics gives you an essential grounding and understanding to how real music sounds behave in different spaces whether during a performance or a recording and how they are perceived by performers and listeners. With their clear and simple style Howard and Angus walk you through the theory- the science of sound engineering and music production, the acoustics of musical instruments, how we hear musical sounds, and the practical- how to apply it to music spaces to create professional sound. Real-world examples and audio clips to work with are provided, providing practical materials to work with. The new edition uncovers the acoustic application for today's recording industry. The accompanying CD provides audio examples to help readers gain a clear understanding of the many concepts discussed in the book The website is packed with audio clips, questions and answers, a calculation facility as well as links and resources. * Acoustics and psychoacoustics covered from a musical standpoint to help those involved in music technology and music understand sound and how we hear it as well as how the acoustics of spaces affect sound transmission and recording spaces * New content includes surround sound standards, MP3/ AAC coding, basics of audiometric measurement, mosquito "teen scarers" * Supporting website with audio clips, recorded sound, illustrates concepts.
Front Cover; Acoustics and Psychoacoustics; Copyright Page; Contents; Preface; CHAPTER 1 Introduction to Sound; CHAPTER 2 Introduction to Hearing; CHAPTER 3 Notes and Harmony; CHAPTER 4 Acoustic Model for Musical Instruments; CHAPTER 5 Hearing Timbre and Deceiving the Ear; CHAPTER 6 Hearing Music in Different Environments; CHAPTER 7 Applications: Acoustics and Psychoacoustics Combined; APPENDIX 1 The Fourier Transform; APPENDIX 2 Solving the ERB Equation; APPENDIX 3 Converting between Frequency Ratios and Cents; APPENDIX 4 Deriving the Reverberation Time Equation.
Previous edition: 2006.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Psychoacoustics; Music -- Acoustics and physics; Sound -- Recording and reproducing -- Digital techniques; PSYCHOLOGY -- Physiological Psychology; Music -- Acoustics and physics; Psychoacoustics; Sound -- Recording and reproducing -- Digital techniques; Electronic books